Educational service quality in Juvenile Detention Centers: inclusivity and national standards - Hendriano Meggy; Yoga Budhi Santoso; Ana Fatimatuzzahra; Kholifatul Novita Ningsih; Anira Zakiyyah Febrianti; Naila Cynthia Fajrin; Wafda Arafah Khairunnisa (Inovasi Kurikulum, 2026)
Education in the Juvenile Detention Center (JDC) plays a strategic role in fulfilling children’s fundamental rights while also serving as a means of rehabilitation and social reintegration. This study aims to analyze the quality of educational service provision across three JDCs, drawing on the National Education Standards and principles of inclusivity. The study employs a qualitative case study design. Data were collected through in-depth interviews with teachers and educational program administrators and were analyzed using thematic analysis. The findings indicate that the fulfillment of educational standards, particularly in terms of curriculum, assessment, and facilities, remains partial. Major gaps were identified in responsive instructional practices, the use of learning media, and the evaluation of educational programs. Although educational access has been provided to all juveniles in care, adaptation to individual learning needs remains limited, and most educators lack specific competencies in inclusive education. These findings suggest that the implementation of inclusivity principles in LPKA remains largely formalistic, resulting in an educational provision that has not yet fully functioned as an effective rehabilitation mechanism due to systemic and institutional constraints. Therefore, more targeted policies, enhanced educator competencies, and stronger inter-agency collaboration are required.   Abstrak Pendidikan di Lembaga Pembinaan Khusus Anak (LPKA) memiliki peran strategis sebagai pemenuhan hak dasar anak sekaligus sebagai sarana rehabilitasi dan reintegrasi sosial. Penelitian ini bertujuan untuk menganalisis kualitas penyelenggaraan layanan pendidikan di tiga LPKA dengan mengacu pada Standar Nasional Pendidikan dan prinsip inklusivitas. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam dengan guru dan pengelola program pendidikan, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa pemenuhan standar pendidikan, khususnya pada aspek kurikulum, asesmen, dan sarana prasarana, masih bersifat parsial. Kesenjangan utama ditemukan pada praktik pembelajaran yang responsif terhadap kebutuhan peserta didik, pemanfaatan media pembelajaran, serta evaluasi program pendidikan. Meskipun akses pendidikan telah diberikan kepada seluruh anak binaan, penyesuaian terhadap kebutuhan individual masih terbatas dan sebagian besar pendidik belum memiliki kompetensi khusus dalam pendidikan inklusif. Temuan ini menunjukkan bahwa penerapan prinsip inklusivitas di LPKA masih bersifat formalistik, sehingga penyediaan pendidikan belum sepenuhnya berfungsi sebagai mekanisme rehabilitasi yang efektif akibat keterbatasan sistemik dan kelembagaan. Oleh karena itu, diperlukan kebijakan yang lebih terarah, peningkatan kompetensi pendidik, serta penguatan kolaborasi antar lembaga. Kata Kunci: inklusivitas; Lembaga Pembinaan Khusus Anak; LPKA; standar nasional pendidikan